SNAREs in the maturation and function of LROs. Issue 1 (2nd January 2016) - Jani, Riddhi Atul; Mahanty, Sarmistha; Setty, Subba Rao Gangi
Abstract: The early/recycling endosomes of an eukaryotic cell perform diverse cellular functions. In addition, the endosomal system generates multiple organelles, including certain cell type-specific organelles called lysosome-related organelles (LROs). The biosynthesis of these organelles possibly occurs through a sequential maturation process in which the cargo-containing endosomal vesicular/tubular structures are fused with the maturing organelle. The molecular machinery that regulates the cargo delivery or the membrane fusion during LRO biogenesis is poorly understood. Here, we describe the known key molecules, such as SNAREs, that regulate both the biogenesis and secretion of multiple LROs. Moreover, we also describe other regulatory molecules, such as Rab GTPases and their effectors that modulate the SNARE activity for cargo delivery to one such LRO, the melanosome. Overall, this review will increase our current understanding of LRO biogenesis and function.